A broad-spectrum phage controls multidrug-resistant Salmonella in liquid eggs. (June 2020) - Li, Zhiwei; Ma, Wenjuan; Li, Wanning; Ding, Yifeng; Zhang, Yu; Yang, Qile; Wang, Jia; Wang, Xiaohong
Graphical abstract: Highlights: A broad-spectrum Salmonella phage D1-2 was isolated and identified. D1-2 exhibited high pH and temperature tolerances together with a low frequency of development of phage resistance. D1-2 controlled the growth of multidrug-resistant Salmonella in highly risky liquid eggs. No virulence and antibiotic resistance-associated genes were identified in the D1-2 genome. Abstract: Salmonella is a foodborne pathogen constantly threating public health. The widespread use of antibiotics and globalization of the food industry result in rapid growth of drug-resistance. Eggs contaminated by multidrug-resistant (MDR) Salmonella are one of the riskiest factors of salmonellosis, which are frequently associated with outbreaks worldwide. Thus, there are increasing needs for the development of new technologies in controlling MDR pathogens and for the confirmation of their practical efficiency in target food matrices. In this study, 43 Salmonella phages were isolated from environmental resources and among them, phage D1-2 was selected since it exhibited the most potent lytic ability and the broadest host spectrum against tested Salmonella strains. Further study demonstrated that D1-2 shows high pH and thermal tolerances and a short latent period, together with a low frequency of emergence of phage resistance. D1-2 effectively inhibited the growth of two MDR Salmonella strains in liquid egg white and egg yolk at both 4 °C and 25 °C. Morphology and phylogeny indicated that D1-2 belongs to the Myoviridae family. Genome analysis of D1-2 revealed a linear dsDNA sequence with no homology to virulence or antibiotic-resistance associated genes, presenting D1-2 is a promising candidate for the biocontrol of MDR Salmonella in highly risky foods.